Penerapan Fungsi Hash dengan Algoritma RIPEMD-128 Pada Aplikasi Duplicate PDF Scanner - Abdurrahman Al Habib (Journal of Computer System and Informatics (JoSYC), 2021)
The development of the digital world era continues to grow and is increasing. Many industries have switched to digital technology such as photos, videos, music, and so on. Of course, this change brings many benefits in terms of speed and data access. Ease of accessing the internet also has a major impact on human life. The ease of accessing documents online is very helpful if you want to find and download pdf documents online. With this convenience, many of the same pdf files are downloaded more than once. This will definitely burden the storage space. To distinguish one pdf file from another, it is done by viewing and reading the contents of the pdf file. This is very inconvenient and time consuming. To overcome this, we need a practical way that can be used to search for the same pdf document so that it can delete duplicate pdf files. One way that can be used to overcome this problem is to use a hash function. The hash function in cryptography is a very important tool in various cryptographic applications, for example in digital signature formation, authentication, and so on. Since the discovery of the MD4 hash algorithm by Ron Rivest, many other hash algorithms have been developed based on the principles of this algorithm. One of them is the RIPEMD-128 algorithm. RIPEMD-128 is an iterative hash function that operates on 32-bit words. By using a hash function, the identity of the pdf file can be generated. If the pdf files are the same it will produce the same hash value as well. This will make it easier to group the same pdf documents so that it will speed up the process of deleting the same pdf files. With the pdf file scanner application, pdf files will be searched for all folders and will group pdf files based on the same hash value. So that it will be easier for users to delete the same pdf file.